How should the chest wall be opened at necropsy?. Issue 1 (1st January 2002) - Walker, J E C; Rutty, G N; Rodgers, B; Woodford, N W F
Abstract : Aims: To compare several different instruments used to open the chest wall during necropsy and to assess whether any one type reduced the production of sharp rib ends and thus the potential for receiving an injury. Methods: During the necropsy the pathologist opened the chest wall using two randomly assigned instruments from a selection of hand saw, electric saw, rib shears, and bread knife. The age, weight, sex, and height of the deceased were recorded, in addition to the textures of the resultant exposed rib ends. During the procedure, the speed, length, production of spray, and site of incision were also noted. The thoracic cavity was inspected and any details of tumours, adhesions, fluid, or organ damage were noted. Results: Twenty four necropsies were carried out on an equal number of men and women. The total number of ribs that were incised was 422, with 206 through the bony aspect (49%). Sixty seven per cent of the bony rib ends were rough, and this was found to be instrument dependent. The rib shears produced the highest number of rough bony and cartilage rib ends. The electric saw produced the smoothest contoured rib ends. Spray occurred in 29% of cases, exclusively with the use of the electric saw. Organ damage was most frequently associated with the use of the bread knife. Conclusion: Rib shears, the instrument most frequently used to open the chest wall, appear to cause the highest frequency of rough, potentially dangerous rib ends. The electric saw produced the smoothest rib ends, both in cartilage and bone, and thus seems to offer the most efficacious method of reducing the potential hazard associated with ragged, spiky bone ends during the opening of the thoracic cavity. Although each of the procedures detailed in this study was shown to have its own advantages and disadvantages, personal preference and operator experience are perhaps the most important factors in ultimately determining the method used.